دراسة مدى تأثير أبعاد التنمية المستدامة على تدفقات الاستثمار الاجنبي المباشر إلى الدول العربية-دراسة تحليلية قياسية خلال الفترة 2007-2018. (Revue El-Wahat pour les Recherches et les Etudes, 2022)
ملخص:  تهدف هذه الورقة البحثية إلى تحديد أي من أبعاد التنمية المستدامة التي لها تأثير على تدفق الاستثمار الأجنبي المباشر إلى الدول العربية، حيث شملت عينة الدراسة 15 دولة عربية خلال الفترة 2007-2018، وقد تم الاعتماد على عديد من أدوات التحليل الاحصائي والقياسي حيث من خلال مقارنة المتوسطات تبين أن هناك تباين في مستوى تدفقات الاستثمار الأجنبي المباشر إلى الدول العربية، وبواسطة التحليل العنقودي اتضح أن هناك ثلاث مجموعات في الدول العربية تم تقسيمها حسب أبعاد التنمية المستدامة وتدفقات الاستثمار الأجنبي.    ومن خلال التحليل الساكن لنماذج البانل تبيّن أن نموذج التأثيرات الفردية الثابتة هو الملائم أي أن مصدر الاختلاف في تدفق الاستثمار الأجنبي المباشر إلى الدول العربية يعود إلى وجود تأثيرات فردية ثابتة قد تعود إلى عوامل عديدة، وأن كل من البعد الاقتصادي والبيئي كان لهما تأثير على تدفق الاستثمار الأجنبي المباشر، في حين أن البعد الاجتماعي لم يكن له تأثير على تدفق الاستثمارات الأجنبية المباشرة إلى الدول العربية.كلمات دالة: استثمار أجنبي المباشر، أبعاد تنمية المستدامة، نمو اقتصادي، بيانات البانل، دول عربية. Abstract:  This research paper aims to define any of the dimensions of sustainable development that have an impact on the flow of foreign direct investment to the Arab countries, as the study sample included 15 Arab countries during the period 2007-2018, was relied on many tools of statistical analysis and econometrics The benchmark, by comparing the averages, shows that there is a variation in the level of foreign direct investment flows to Arab countries, while the cluster analysis showed that there are three groups in the Arab countries that have been divided according to the dimensions of sustainable development and foreign investment flows.    Through static analysis of the panel models, it was found that the fixed individual effects model is appropriate, that is, the source of the difference in the flow of foreign direct investment to Arab countries is due to the presence of fixed individual effects that may be due to many factors, and that both the economic and environmental dimension had an impact on the flow Foreign direct investment, while the social dimension had no effect on the flow of foreign direct investment to Arab countries Key words: foreign direct investment, dimensions of sustainable development, economic growth, panel data, Arab countries